Knowledge, attitudes, perception and practices regarding antiretroviral therapy among HIV-infected adults in Antananarivo, Madagascar: a cross-sectional survey - Mihaja Raberahona; Zinara Lidamahasolo; Johary Andriamamonjisoa; Volatiana Andriananja; Radonirina Lazasoa Andrianasolo; Rivonirina Andry Rakotoarivelo; Mamy Jean de Dieu Randria (BMC, 2019)
Abstract Background Adherence to antiretroviral therapy (ART) may be influenced by knowledge, perception and perception regarding ART. The purpose of this study was to assess knowledge, attitude/perception and practice regarding ART among people living with HIV/AIDS (PLHIV). Methods We conducted a cross-sectional survey to assess knowledge, attitudes, perception and practices ART in PLHIV. The survey was suggested to all PLHIV of at least 18 years old and who were on ART for at least 1 month. PLHIV who were unable to answer questions correctly and those who did not complete the survey for any reason were excluded. Results During the study period, 234 PLHIV were included. Participants were mostly men (75.2%). The median age was 33 years (IQR: 27-41). The median time since HIV diagnosis was 25 months (IQR: 9-56) and the median duration of ART was 18 months (IQR: 8-48). 87.6% had an overall good knowledge of ART. However, only 3.2% knew the name of their ART, 31.2% were aware that ART should be taken at a fixed time and 17.1% knew how to take ART in relation to food intake. 75.6% of participants had an overall positive attitude/perception of ART. However, 10.7% were convinced that other methods were more effective than ART for treating HIV and 42.7% thought that taking ART was shameful. The assessment of practices showed that in case of missed dose, 48.3% of participants routinely skipped this dose instead of trying to take it as soon as possible. In multivariate analysis, good knowledge of ART was independently associated with high level of education (aOR: 4.7, IC95%: 1.6-13.7, p = 0.004) and disclosure of HIV status (aOR: 2.7, IC95%: 1.1-6.6, p = 0.029). Conclusions This study showed an overall good knowledge and a predominantly positive attitude/perception of ART. However, accurate knowledge of ART intake was insufficient and the stigma associated with taking ART remained very present. Furthermore, very heterogeneous practices may reflect lack of instruction given by the physician regarding ART intake.